Neoliberalismo e destruição da democracia : uma abordagem marxista na ciência política - Carlos Estevão Caligiorne Cruz (2019)
The concept of neoliberalism still represents a major challenge for the political science scholarship and normative theories about democracies; however, this concept is crucial in any theorizing about the current dilemmas of contemporary democratic regimes. This dissertation takes this challenge of doing the conceptual work of neoliberalism in political science seriously. This study proposed to interpret, with its mediations, he political meaning of neoliberalism for democracy. The dissertation is developed through five major theoretical and methodological steps. First, it analyzes the growing scholarship that has mobilized the concept of neoliberalism to problematize the deep dilemmas of contemporary democracies. Second, the dissertation welcomes the broad contemporary literature about neoliberalism, manly published in English, aiming to, in one hand, bring the debate around the concept to the Brazilian scholarship, on the other hand, aiming to integrate this effort through conceptualizing the political character of neoliberalism. Third, the dissertation leads this conceptual work relying on contemporary Marxist political theory, incorporating the praxiological and critical perspectives of this approach, which helps to understand the historical trends that shape the political action, also contributing to its consistency and relevance as a field analytical-normative approach of Political Science. Fourth, the dissertation also discusses the construction of a neoliberal political language built in which certain social actors rely upon to legitimate the construction of this new hegemonic order according to their conception of the world. This fourth approach relies on the foundations and historical development of the neoliberal political theories, particularly proposing a systematic analysis of the political philosophy of Hayek, and its organic unity between politics and economics which constitutes the political will to construct this new hegemonic order. To conclude, the fifth step discusses changes in constitutional regimes and State’s political regulations, connecting the political meaning of neoliberalism to a long-term view regarding historical and structural conflicts between Capitalism and Democracy, and hegemonic liberalism. Through this work, the dissertation argues that neoliberalism has a de-democratizing meaning characterized by a progressive undoing of contemporary democracies and the constitutionalizing of new, non-democratic structures of power. This de-democratizing sense is inscribed in the historical tendencies of the neoliberal era that forms its fields of possibility and shapes the action of political actors in the present time.